Impact of personality and structural design on job satisfaction among bank workers (2001)
The aim of the study was to examine the impact of personality and changes in office design on employees job satisfaction among bankers. The 98 participants were drawn from 4 commercial banks in 2 southwestern cities namely Lagos and Ibadan. The participants had a mean age of 51 years and standard deviation of 3.85 for males and a mean age of 32 years and a standard deviation of 3.3 for female participants. The instrument used for the collection of data were the introversion (extraversion scales of the Eysenck personality Questionnaire, and job satisfaction index. Result showed that Extroverts (mean = 65: 74) experienced significantly higher job satisfaction than introverts (mean = 58.84), F=(1,94) = 8.50, p<.05. Employees in open systems (mean=63.56) experienced significantly higher job satisfaction than those in closed systems (mean=57.32) F=(1,94)=6.29, p<.05. However, personality and office design did not show significant interaction effect on job satisfaction F(1,94)=1.25, p<.O5 The implication of the study are that banks and other service organization need to ascertain the suitability of their workers to different job conditions. Similarly, the importance of workplace/ environment design and its overbearing effects on employee productivity need to be recognized by service and manufacturing organizations